Reconsidering the Acquisition Planning for English in favour of the EMI Implementation’s Prospects in the Algerian Higher Education: Expert Recommendations and Suggestions. - Mr. Ahmed Lotfi BELAREF, Ms. Intissar NourElhak MHAMDIA (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
The acquisition planning process is the central component of any language planning activity, and the latter is yet the heart of any effective language policy. In this light, this study aims at investigating the necessity of reconsidering the acquisition planning for English at the pre-university levels as part of the planning for the prospects of implementing English as a medium of instruction (EMI) at the Algerian higher educational level and at providing expertdriven recommendations to teaching English as a foreign language (EFL) at the Algerian preuniversity levels as part of the acquisition planning. The study was conducted following a fixed design with little inclusion of qualitative data collection. A questionnaire was used as the main instrument in the study to collect the primary data and was administered to 22 participants. The participants in this study were selected through the purposive sampling technique based on their scientific publications in the domain and their teaching careers as field practitioners. The findings of the study confirmed that the prospects of implementing EMI in the Algerian higher education require a deep reconsideration and renovation of EFL teaching nature at Preuniversity levels as part of the planning. Moreover, the results highlighted a set of normative practices as part of the acquisition planning for English to precede and be in favour of EMI implementation.
Keywords: Key words: Language Planning, Acquisition Planning, Language policy, Pre-university levels, Algerian higher education, EMI implementation, EFL teaching.